2020
DOI: 10.7554/elife.59328
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous somatostatin-expressing neuron population in mouse ventral tegmental area

Abstract: The cellular architecture of the ventral tegmental area (VTA), the main hub of the brain reward system, remains only partially characterized. To extend the characterization to inhibitory neurons, we have identified three distinct subtypes of somatostatin (Sst)-expressing neurons in the mouse VTA. These neurons differ in their electrophysiological and morphological properties, anatomical localization, as well as mRNA expression profiles. Importantly, similar to cortical Sst-containing interneurons, most VTA Sst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(43 citation statements)
references
References 63 publications
3
40
0
Order By: Relevance
“…Given that GABAergic VTA cells are heterogeneous ( 13 , 27 , 28 ), and only a subset of VTA Vgat cells responded to SDS (Fig. 2B), we looked for subtypes of VTA GABA cells responsible for SDS-induced sleep.…”
Section: Vta Somatostatin Neurons Are Necessary For Sds-induced Sleepmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that GABAergic VTA cells are heterogeneous ( 13 , 27 , 28 ), and only a subset of VTA Vgat cells responded to SDS (Fig. 2B), we looked for subtypes of VTA GABA cells responsible for SDS-induced sleep.…”
Section: Vta Somatostatin Neurons Are Necessary For Sds-induced Sleepmentioning
confidence: 99%
“…S16, A and B). Because VTA Sst cells are heterogeneous ( 28 ), we examined the molecular identities of SDS-tagged cells (fig. S16C).…”
Section: Vta Somatostatin Neurons Are Necessary For Sds-induced Sleepmentioning
confidence: 99%
“…In addition to the presence of serotonergic cell bodies, dopaminergic cell bodies are also distributed in the VTA [ 165 ], an area of the brain that plays a role in reward-processed, and regulation of emotion and cognitive behaviours [ 166 ]. Although the neuropharmacological mechanisms of action of psilocybin are not definitively elucidated, there is evidence that, in addition to interaction with the serotonergic system, psilocybin also seems to interact, though not directly, with the mesolimbic dopaminergic pathway that plays a significant role in the brain’s reward system [ 165 ].…”
Section: Psilocybin Synthesismentioning
confidence: 99%
“…3c, 4b). We previously demonstrated that different electrophysiological subtypes of the VTA Sst neurons have distinct locations, assigning anterolateral VTA neurons to either afterdepolarizing (ADP) or high-frequency firing (HFF) subtypes (Nagaeva et al, 2020). Therefore, we took an effort to define the electrophysiological subtype of the projecting neurons.…”
Section: The Majority Of Vta Sst Projecting Neurons Have Electrophysi...mentioning
confidence: 99%